2017
DOI: 10.1016/j.jcis.2016.10.054
|View full text |Cite
|
Sign up to set email alerts
|

High temperature ultralow water content carbon dioxide-in-water foam stabilized with viscoelastic zwitterionic surfactants

Abstract: Ultralow water content carbon dioxide-in-water (C/W) foams with gas phase volume fractions (ϕ) above 0.95 (that is <0.05 water) tend to be inherently unstable given that the large capillary pressures that cause the lamellar films to thin. Herein, we demonstrate that these C/W foams may be stabilized with viscoelastic aqueous phases formed with a single zwitterionic surfactant at a concentration of only 1% (w/v) in DI water and over a wide range of salinity. Moreover, they are stable with a foam quality ϕ up to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(52 citation statements)
references
References 62 publications
0
52
0
Order By: Relevance
“…The stabilization is also favored by maintaining sufficiently thick lamellae upon slowing down lamellae drainage to the plateau borders . An emerging understanding of foam stability in terms of interfacial properties is of great value for foam design in a wide variety of applications, including mobility control for the flow of gases in enhanced oil recovery in subsurface reservoirs. …”
Section: Introductionmentioning
confidence: 99%
“…The stabilization is also favored by maintaining sufficiently thick lamellae upon slowing down lamellae drainage to the plateau borders . An emerging understanding of foam stability in terms of interfacial properties is of great value for foam design in a wide variety of applications, including mobility control for the flow of gases in enhanced oil recovery in subsurface reservoirs. …”
Section: Introductionmentioning
confidence: 99%
“…1,2 As an important type of zwitterionic surfactant, betaines have a hydrophilic headgroup comprised of a quaternary ammonium group and an anionic group such as carboxylate, sulfonate, sulfate, or phosphate. 3 Betaine-type surfactants possess distinctive physicochemical properties such as high foam stability, skin and eye compatibility, high efficiency in lowering surface tension, and low toxicity, 4 leading to a wide range of applications in enhanced oil recovery, [5][6][7] detergents, 8,9 cosmetics 2,10 and textile production. 11 As the geometry of betaine-type surfactants has a signicant effect on their physicochemical properties, considerable efforts have been devoted to their structural optimization.…”
Section: Introductionmentioning
confidence: 99%
“…Xue et al (2015) reported a high-viscosity foam produced by using CO 2 soluble ionic surfactants at a temperature of 120 °C and a saltwater TDS content of 14.6%. Recently, Alzobaidi et al (2017) reported the use of zwitterionic surfactants to prepare highly stable foams with a viscosity in excess of 100 cP at 120 °C.…”
Section: Asp Flooding and Foam Floodingmentioning
confidence: 99%